Abundance of arthropod pests and their natural enemies on cassava fields implementing different agroecosystem management - RETNO DYAH PUSPITARINI; ALDY PURWANTORO; VANADYA DECEMBRY ALODYA PRADIFTA; FAIZ NASHIRUDDIN MUHAMMAD; ITO FERNANDO (Society for Indonesian Biodiversity, 2024)
Abstract. Puspitarini RD, Purwantoro A, Pradifta VDA, Muhammad FN, Fernando I. 2024. Abundance of arthropod pests and their natural enemies on cassava fields implementing different agroecosystem management. Biodiversitas 25: 2901-2907. Arthropod pests pose significant challenges to cassava (Manihot esculenta Crantz) cultivation, with detrimental effects on yield and crop quality. Agroecosystem management plays a crucial role in shaping the populations of pests and their natural enemies. Therefore, understanding and implementing appropriate management practices are essential for developing integrated pest management approaches that are effective and environmentally friendly. Our study examined herbivorous and predatory arthropod abundance across six cassava plantations with varying management practices. Field characteristics were examined to elucidate the factors contributing to differences in arthropod assemblages observed among the fields. We used Analysis of Variance (ANOVA) to assess the differences in arthropod abundance across the plantations. Additionally, arthropod assemblage was analyzed using analysis of similarity based on the Bray-Curtis Index, with differences visualized using non-metric multidimensional scaling (NMDS) plots. The high abundance of herbivorous arthropods in certain fields appeared linked to narrow plant spacing, which might facilitate pest dispersal. Furthermore, complete weed removal and the absence of organic fertilizer application, such as manure, could reduce predatory arthropod populations. Additionally, fields situated at lower altitudes demonstrated increased susceptibility to pest outbreaks. Therefore, strategic agroecosystem management is imperative, incorporating practices to mitigate pest population growth while conserving predatory arthropods. Comprehending the interplay between management practices and arthropod dynamics is crucial for developing sustainable pest management strategies in cassava cultivation.